Biomass allocation and root topology alteration of an introduced amphibious plant in response to cultural eutrophication - Xiaolong Huang; Yu Zhao; Hai Xu; Chunyu Yin; Ruijie Shen; Baohua Guan; Zhigang Mao; Hu He; Jinlei Yu; Kuanyi Li (Ecosphere, 2024)
Abstract Parrot feather (Myriophyllum aquaticum) is an introduced, noninvasive amphibious plant found in coastal provinces, but it has the potential to become an invasive species in China. The plant is heterophyllous, with both emergent (aerial) and submerged (aquatic) leaves, and has two distinct root types: aquatic (adventitious) and edaphic (sediment) root systems. This morphological plasticity allows M. aquaticum to effectively absorb nutrients from different layers of the environment, making it a suitable model plant for exploring nutrient dynamics in both water and soil systems and investigating how wetland plants respond to cultural eutrophication. We designed an outdoor mesocosm experiment to assess plant growth traits and root topological indices in response to different nitrogen (N) and phosphorus (P) concentrations. The results indicated that the plant has a high tolerance to N loading. In contrast, the P content had greater impacts than the N content on plant growth and root topological indices, indicating that the P content was the main influencing factor affecting and suppressing the development of M. aquaticum. The aquatic or edaphic root branching did not change, but the aquatic root topology of M. aquaticum exhibited similar stable trends with increasing P concentration, indicating typical herringbone branching; additionally, its edaphic roots exhibited decreasing topological indices, indicating more typical dichotomous branching with increasing P concentration. The plant has a high tolerance to N, and it may become invasive following the current trend of increasing cultural eutrophication.